Preconditions for a valid consent under the General Data Protection Regulation - Nagle, Terēze (Riga Graduate School of Law, 2020)
For the data processing to be legal and valid in the European Union, the General Data Protection Regulation has to be followed. Article 6(1) of the Regulation sets out the options by which the data controller should comply with the law when the processing of data takes place. In reality, it does not always happen. Consent, as one of the options, is discussed and analysed in this Thesis. The author researches how effective the GDPR is in regard to the preconditions it imposes for a valid consent and what are the main areas where the data controller cannot comply with these requirements. An analysis of selected cases clearly demonstrates that the prerequisite for consent to be informed is breached the most. The consent forms of various organizations show that there are a number of challenges in drafting consent. Pre-ticked boxes were an example of the infringement done to the Regulation.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Data protection